2006
DOI: 10.1074/jbc.m601770200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Expressed Form of Human Cytosolic Phospholipase A2β (cPLA2β)

Abstract: In this study, we identify the principal splice variant of human cytosolic phospholipase A 2 ␤ (cPLA 2 ␤) (also known as Group IVB cPLA 2 ) present in cells. In human lung, spleen, and ovary and in a lung epithelial cell line (BEAS-2B), cPLA 2 ␤ is expressed as a 100-kDa protein, not the 114-kDa form originally predicted. Using RNA interference, the 100-kDa protein in BEAS-2B cells was confirmed to be cPLA 2 ␤. BEAS-2B cells contain three different RNA splice variants of cPLA 2 ␤ (␤1, ␤2, and ␤3). cPLA 2 ␤1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…The similar inhibitor sensitivity of cPLA 2 and cPLA 2 ␣ is in contrast to the results with mouse cPLA 2 ␤, which is not inhibited by pyrrolidine-2 and Wyeth-1. Human cPLA 2 ␤ and human cPLA 2 ␥ also are not inhibited by pyrrolidine-2 and pyrrolidine-1, respectively (22,39). The basis for the differences in sensitivity of the GIV PLA 2 family to pyrrolidine-2 and Wyeth-1 is not clear at this time.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The similar inhibitor sensitivity of cPLA 2 and cPLA 2 ␣ is in contrast to the results with mouse cPLA 2 ␤, which is not inhibited by pyrrolidine-2 and Wyeth-1. Human cPLA 2 ␤ and human cPLA 2 ␥ also are not inhibited by pyrrolidine-2 and pyrrolidine-1, respectively (22,39). The basis for the differences in sensitivity of the GIV PLA 2 family to pyrrolidine-2 and Wyeth-1 is not clear at this time.…”
Section: Discussionmentioning
confidence: 91%
“…We recently reported that human cPLA 2 ␤ also has low enzymatic activity and that neither mouse nor human cPLA 2 ␤ is inhibited by cPLA 2 ␣ inhibitors (22). Analysis of the mouse cPLA 2 ␤ transcript present in lung fibroblasts demonstrates that it does not contain the truncated JmjC domain found in the N terminus of human cPLA 2 ␤.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations